Introduction: Exploring entrepreneurial activity and small business issues in the Chinese economy. (September 2014) - Cumming, Douglas; Guariglia, Alessandra; Hou, Wenxuan; Lee, Edward; Newman, Alex
This introduction summarises the International Small Business Journal special issue on 'Exploring Entrepreneurial Activity and Small Business Issues in the Chinese Economy' and discusses the future research agenda.